Designing services and programs for high-ability learners a guidebook for gifted education - Robins, Jennifer H.; Eckert, Rebecca D. (Corwin, a SAGE Company, 2017)
The updated, comprehensive guide to developing or enhancing gifted programming How do we ensure we are meeting the needs of gifted students? The educational landscape has changed dramatically since Designing Services and Programs for High-Ability Learners was first published in 2006. This updated and revised second edition of the landmark guidebook provides educators and administrators with the comprehensive, practical advice they need to support gifted learners, and includes new perspectives based on recent research and the updated National Association for Gifted Children Programming Standards. Written by leading experts, each chapter focuses on a key feature of high-quality gifted programs, from identification to evaluation and advocacy, and takes into account current trends in education.